Perancangan Dan Implementasi Smart Adaptor Berbasis PID Pada Laptop Untuk Manajemen Untuk Optimalisasi Daya Baterai - YOLINVIANUS PAULUS KAKO (Jurnal Qua Teknika, 2024)
This research aims to develop a PID-based Smart Adaptor for laptops to optimize Battery charging processes and enhance Battery lifespan. Laptops are commonly used devices by students and office workers; however, the majority of users often neglect Battery health and maintenance. Suboptimal Battery charging can lead to performance degradation and reduced Battery lifespan. In this study, we design and produce a device that automatically regulates current and voltage to the laptop's Battery using PID control. Testing of this device demonstrates its success in maintaining Battery health and optimizing charging according to the laptop's needs. The device is also capable of protecting the Battery from damage caused by overcharging. The PID method proves effective in controlling Battery voltage towards the established set point. Test results show that the use of the Smart Adaptor with PID control can shorten Battery charging time compared to the laptop's built-in charger. Additionally, this device provides convenience to users as the laptop automatically disconnects when the Battery is full and begins charging when the Battery is nearly depleted.